(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
Archeological discoveries in the city of Mantua over recent decades have helped identify an area that various elements have been identified as a sacred area dating back as far as the arcaic period. Three engraved inscriptions on the pottery left as votive offerings are dedication to Vei and Zipni, female divinities. Vei corrisponds to greek Demeter and also Kore and was worshipped in several sities of Southern Etruria and at Mantua, Felsina, Marzabotto, Servirola di San Polo d’Enza and Parma. Dis Pater was her partner, the most important divinity of the Etruscan dodecapolis in the Po Valley, known as Mantus. The presence of Vei in Mantua can means the presence of Dis Pater/Mantus. Paleografic and onomastic data of some engraved inscription highlights the presence of Celtic worshippers.